2020
DOI: 10.1210/endrev/bnaa032
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Complexity of GLP-1 Action from Sites of Synthesis to Receptor Activation

Abstract: Glucagon-like peptide-1 (GLP-1) is produced in gut endocrine cells and in the brain, and acts through hormonal and neural pathways to regulate islet function, satiety, and gut motility, supporting development of GLP-1 receptor (GLP-1R) agonists for the treatment of diabetes and obesity. Classic notions of GLP-1 acting as a meal-stimulated hormone from the distal gut are challenged by data supporting production of GLP-1 in the endocrine pancreas, and by the importance of brain-derived GLP-1 in the control of ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
140
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(162 citation statements)
references
References 232 publications
(357 reference statements)
0
140
0
3
Order By: Relevance
“…Incretin effects of GLP-1 have been discovered in the 1980s, and they have been successfully exploited for pharmacological glucoregulation by the 2000s [85]. Nevertheless, the physiology of the GLP-1 is still actively explored, and many of its exciting roles are yet to be fully understood [43,86]. It has been proposed that brain GLP-1Rs are involved in the regulation of peripheral glucose homeostasis, fuel partitioning, and monitoring energy levels to prepare the organism for the fasting that comes after a meal [43,59].…”
Section: Brain-gut Glp-1 Axismentioning
confidence: 99%
“…Incretin effects of GLP-1 have been discovered in the 1980s, and they have been successfully exploited for pharmacological glucoregulation by the 2000s [85]. Nevertheless, the physiology of the GLP-1 is still actively explored, and many of its exciting roles are yet to be fully understood [43,86]. It has been proposed that brain GLP-1Rs are involved in the regulation of peripheral glucose homeostasis, fuel partitioning, and monitoring energy levels to prepare the organism for the fasting that comes after a meal [43,59].…”
Section: Brain-gut Glp-1 Axismentioning
confidence: 99%
“…The mechanisms behind the cardioprotective properties of GLP-1RAs are still unclear. Studies have demonstrated that GLP-1RAs exert a direct effect on the heart and blood vessels 6 and an indirect effect via improved glycaemia 24 , a reduction in blood pressure and postprandial rise in triglycerides 25 , a reduction in markers of oxidative stress and systemic inflammation 26,27 (Figure 3). The reduction in MACE observed with treatment with GLP-1RAs is mainly driven by a significant reduction in fatal or non-fatal stroke, but also a significant reduction in risks for CV death and fatal or non-fatal myocardial infarction 15 , suggesting that GLP-1RAs may exert their cardioprotective effects through anti-atherosclerotic mechanisms.…”
Section: Cardioprotective Mechanisms Of Actionmentioning
confidence: 99%
“…Brain-derived GLP-1 act as a neurotransmitter and can target multiple GLP-1Rs throughout the central nervous system, including effects on satiety 6 . In addition, GLP-1R activation in the brain have been linked to neuroprotective properties in experimental neurodegenerative disease models 6 . Deduced from both preclinical and human studies, GLP-1 has extra-pancreatic effects in the gut, kidney, nervous system, heart and immune system (Figure 1) 2 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations